68.0k views
2 votes
Simplify. Rewrite the expression in the form b^nb n b, start superscript, n, end superscript. \dfrac{b^{8}}{b^2}= b 2 b 8 ​ =start fraction, b, start superscript, 8, end superscript, divided by, b, squared, end fraction, equals

User Qqq
by
5.1k points

2 Answers

6 votes

Answer:

the answer is b to the 6th

Explanation:

User Richard Denton
by
5.7k points
6 votes

9514 1404 393

Answer:

b^6

Explanation:

The applicable rule of exponents is ...

(a^b)/(a^c) = a^(b-c)

__


(b^8)/(b^2)=b^(8-2)=\boxed{b^6}

User BEvans
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.